Labor docente respecto a la formación de ciudadanos críticos (2013)
It is anticipated that education plays an important role in society, forcing a certain way for a teacher to strive to be a former student with critical observation skills and boost your search reality reflection to generate social change existing situations by changing thinking and acting. This ability develops in students a sense of understanding and analysis about the world around them, identifying causes and consequences of current events. It is for this reason that the fundamental purpose of this essay is to stimulate argumentative thinking of readers who practice mainly teaching, about the importance and extent of the role played by teachers in training Colombian students critical public awareness that contribute in the short, medium or long term, to make valuable contributions in the social change that demand our country, characterized by a particular context against other states and whose hope of change could be based on the coverage and quality of education of its population.